A fibrous rod-like manganese-rich precursor and a method for preparing the same
Patent Information
- Application Number
- CN202610944336.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-20
AI Technical Summary
然而,传统共沉淀法制备的前驱体多为不规则的团聚颗粒或较为致密的球形颗粒,难以形成兼具特定形貌(如棒状、纤维状)和多孔结构的理想前驱体
1、通过独特的“共沉淀-液相氧化”工艺,在在前驱体氢氧化物层间中协同引入了外源高价金属阳离子A(n≥3)和原位氧化的Mn。为了平衡层板上因此产生的净正电荷,带负电的磷酸根阴离子被驱动进入层间区域并嵌入晶格,替代部分氢氧根OH-,形成层状双金属氢氧化物(LDHs),从而实现了磷元素在前驱体中的高浓度、均匀体相掺杂,这是传统共沉淀法难以实现的技术突破。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy battery materials, and mainly to a fibrous rod-shaped manganese-rich precursor and its preparation method. Background Technology
[0002] Manganese-rich cathode materials, especially lithium-rich manganese-based layered oxides (LMR-NCM), are considered one of the most promising cathode materials for next-generation high-energy-density lithium-ion batteries due to their extremely high theoretical specific capacity (exceeding 300 mAh / g) and the advantages of abundant manganese resources and low cost. However, manganese-rich cathode materials still face many challenges in practical applications: 1) Low initial coulombic efficiency, usually accompanied by irreversible oxygen release during the first charge; 2) Severe voltage decay during cycling, due to the irreversible transformation of the layered structure to the spinel / rock salt phase and the migration of transition metal ions during charge and discharge; 3) Structural instability at high voltages, especially at charging cutoff voltages above 4.5V, where lattice oxygen overflow not only leads to capacity loss but also causes side reactions with the electrolyte, generating gas and posing serious safety hazards.
[0003] To address these issues, researchers have employed various modification strategies, such as bulk doping, surface coating, and morphology control. Bulk doping is considered an effective method for fundamentally stabilizing the crystal structure of materials. Phosphorus, due to its ability to form strong covalent PO bonds with oxygen, is considered an ideal dopant element for stabilizing lattice oxygen and suppressing oxygen overflow. However, traditional doping methods often struggle to achieve uniform, high-concentration phosphorus doping within the material. Directly mixing and sintering the phosphorus source with the precursor via solid-state methods tends to lead to phosphorus enrichment on the particle surface, failing to penetrate the bulk phase to stabilize the structure. Furthermore, traditional coprecipitation methods, limited by charge balance, struggle to efficiently introduce anionic groups such as phosphate groups into the layered structure of hydroxide precursors.
[0004] Furthermore, the microstructure and structure of the precursor have a crucial impact on the electrochemical performance of the final cathode material. Precursors with high specific surface area and loose porous structures are beneficial for the uniform mixing of lithium salts and the full intercalation of lithium ions during subsequent sintering, while also alleviating volume change stress during charge and discharge, thus improving the rate performance and cycle stability of the material. However, precursors prepared by traditional co-precipitation methods are mostly irregular aggregated particles or relatively dense spherical particles, making it difficult to form ideal precursors that combine specific morphologies (such as rod-like or fibrous) and porous structures.
[0005] Therefore, developing a new method for preparing manganese-rich precursors that can achieve high-concentration, uniform bulk doping of phosphorus and construct specific microstructures is of great theoretical significance and practical application value for promoting the commercialization of high-performance, long-life, and high-safety manganese-rich cathode materials. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this application is to provide a fibrous rod-shaped manganese-rich precursor and its preparation method. By introducing phosphorus and high-valence metal elements during the precursor synthesis process, a manganese-rich precursor with a layered hydrotalcite structure, a unique fibrous rod morphology, and a loose and porous interior is synthesized, and a controllable and efficient method for preparing this precursor is provided. The manganese-rich cathode material prepared from this precursor exhibits excellent high-voltage cycle stability and lower voltage decay.
[0007] The technical solution of this application is as follows: A fibrous rod-shaped manganese-rich precursor with the molecular formula [Ni 1-x-y-z Co y Mn z R x (OH) 2-2x (PO4) nx / 3 ;0.03≤x≤0.12, 0≤y≤0.1, 0.5≤z≤0.75; R x For A x1 Mn x2 x1 + x2 = x, A is an n-valent metal ion, R x In this case, Mn and A are both n-valent, n≥3, 0.01≤x1<0.12, 0<x2≤0.11.
[0008] Furthermore, the primary particles of the fibrous rod-shaped manganese-rich precursor have a slender strip shape and are stacked in layers along the 001 crystal plane.
[0009] Furthermore, the average D50 of the fibrous rod-shaped manganese-rich precursor is 2~4 μm; The average pore volume of the fibrous rod-shaped manganese-rich precursor is 0.2~0.6 cm³. 3 / g; The specific surface area of the fibrous rod-shaped manganese-rich precursor is 50~100m². 2 / g; The tap density of the fibrous rod-shaped manganese-rich precursor is 0.8~1.3 g / cm³. 3 .
[0010] Furthermore, the fibrous rod-shaped manganese-rich precursor comprises the following raw materials: a manganese-containing mixed salt solution, a phosphate solution, a precipitant, an oxidant, and an A metal salt solution; The molar ratio of manganese in a manganese-containing mixed salt to metal A in a metal A salt is 75:1 to 25:6.
[0011] The molar ratio of the oxidant to metal A in the metal salt A is 1:5 to 5:1.
[0012] The molar ratio of phosphate ions in phosphate to metal A in metal A salt is 1:1 to 12:1.
[0013] Furthermore, the manganese-containing mixed salt solution is a nickel-manganese mixed salt solution or a nickel-cobalt-manganese mixed salt solution.
[0014] Furthermore, the manganese-containing mixed salt solution includes one or more of sulfates, chlorides, nitrates, and acetates.
[0015] Furthermore, the phosphate in the phosphate solution includes one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, sodium monofluorophosphate, and ammonium monofluorophosphate. The precipitant includes one or both of NaOH solution and KOH solution; The oxidant includes one or more of the following: a nitrogen-oxygen mixture, hydrogen peroxide solution, ammonium thiosulfate solution, and sodium thiosulfate solution; The metal salt solution A includes solutions containing one or more soluble metal salts selected from Mn, Al, Fe, Ti, Zr, Nb, Mo, and W.
[0016] Furthermore, the concentration of the manganese-containing mixed salt solution is 1.0~3.0 mol / L; The concentration of the phosphate solution is 0.25~1.0 mol / L; The concentration of the precipitant is 2.7~10.8 mol / L; The concentration of the metal salt A solution is 0.1~0.5 mol / L.
[0017] This application also provides a method for preparing a fibrous rod-shaped manganese-rich precursor, comprising the following steps: mixing a precipitant with water to obtain a base solution with a pH value of 10.0~11.0; Under conditions of 30~60℃, stirring speed of 550~700rpm, and inert atmosphere, the base liquid, manganese mixed salt solution, phosphate solution, metal A salt solution, and oxidant are mixed and reacted at pH 10.0~11.0 for 60~90min. After the above reaction is completed, the mixture is reacted for 50-60 hours under the conditions of pH 9.0-10.0, temperature 30-60℃, and continuous oxidant flow to obtain the slurry. The precipitant is continuously introduced during the above preparation process, and the pH is adjusted by controlling the amount of precipitant introduced. The slurry was washed, centrifuged, dehydrated, and dried to obtain a fibrous rod-shaped manganese-rich precursor.
[0018] Furthermore, the color of the slurry was quantitatively determined using a Lab colorimeter, and the L value of the slurry was 55~65, the a value was 3~10, and the b value was 15~30.
[0019] Compared with the prior art, this application has the following beneficial effects: 1. Through a unique "co-precipitation-liquid phase oxidation" process, exogenous high-valence metal cations A (n≥3) and in-situ oxidized Mn are synergistically introduced into the interlayer of the precursor hydroxide. To balance the net positive charge generated on the layers, negatively charged phosphate anions are driven into the interlayer region and embedded in the lattice, replacing some hydroxyl ions (OH-) to form layered bimetallic hydroxides (LDHs). This achieves high-concentration, uniform bulk doping of phosphorus in the precursor, a technological breakthrough that is difficult to achieve with traditional co-precipitation methods.
[0020] 2. The precursor prepared in this application exhibits a fibrous rod-like morphology, with an inherent loose porous structure and a huge specific surface area (up to 95 m²). 2 The porous structure significantly increases the reaction interface with lithium salts, promoting lithiation reactions during both low-temperature pre-sintering and high-temperature main sintering stages. This allows lithium to be more fully and uniformly embedded into the material's crystal lattice, facilitating the formation of cathode materials with lower cation mixing, higher crystallinity, and more uniform elemental distribution. Simultaneously, the porous structure provides abundant channels for the rapid transport of lithium ions within the cathode material, thereby significantly improving its rate performance.
[0021] 3. Uniformly doped phosphorus and high-valence metal elements can form more stable oxygen-containing covalent bonds with oxygen in the crystal lattice during subsequent high-temperature sintering. These strong chemical bonds can effectively anchor lattice oxygen and suppress irreversible phase transitions and structural collapse caused by lattice oxygen extraction under high-voltage (e.g., 4.5V or even higher) charging conditions. Attached Figure Description
[0022] Figure 1 The images show a surface view (a), a cross-sectional SEM image (b), and an XRD pattern (c) of the fibrous rod-shaped manganese-rich precursor of Example 1 of this application.
[0023] Figure 2 The images show a surface view (a), a cross-sectional SEM image (b), and an XRD pattern (c) of the fibrous rod-shaped manganese-rich precursor of Example 2 of this application.
[0024] Figure 3 The images show a surface view (a), a cross-sectional SEM image (b), and an XRD pattern (c) of the manganese-rich precursor of Comparative Example 1 of this application.
[0025] Figure 4 The images show a surface view (a), a cross-sectional SEM image (b), and an XRD pattern (c) of the manganese-rich precursor of Comparative Example 2 of this application.
[0026] Figure 5 The images show a surface view (a), a cross-sectional SEM image (b), and an XRD pattern (c) of the manganese-rich precursor of Comparative Example 3 of this application. Detailed Implementation
[0027] This application provides a fibrous rod-shaped manganese-rich precursor and its preparation method. To make the objectives, technical solutions, and effects of this application clearer and more explicit, the following provides a more detailed description. It should be understood that the specific embodiments described herein are merely illustrative of this application and are not intended to limit the scope of this application.
[0028] This application provides a fibrous rod-shaped manganese-rich precursor, which is a layered bimetallic hydroxide (LDH).
[0029] The molecular formula of the fibrous rod-shaped manganese-rich precursor is [Ni 1-x-y-z Co y Mn z R x (OH) 2-2x (PO4) nx / 3 Where, 0.03≤x≤0.12, 0≤y≤0.1, 0.5≤z≤0.75; R x Specifically, A x1 Mn x2 x1 + x2 = x, A is an n-valent metal ion, R x In this case, Mn and A are both n-valent, n≥3, 0.01≤x1<0.12, 0<x2≤0.11.
[0030] The fibrous rod-shaped manganese-rich precursor is fibrous rod-shaped, with the primary particles having a slender strip morphology and being stacked in layers along the 001 crystal plane.
[0031] The average D50 of the fibrous rod-shaped manganese-rich precursor is 2–4 μm; the average pore volume of the fibrous rod-shaped manganese-rich precursor is 0.2–0.6 cm³. 3 / g; the specific gravity of the fibrous rod-shaped manganese-rich precursor is 50~100m 2 / g.
[0032] The tap density of the fibrous rod-shaped manganese-rich precursor is 0.8~1.3 g / cm³. 3 ; The X-ray diffraction pattern of the fibrous rod-shaped manganese-rich precursor exhibits typical LDHs characteristic diffraction peaks near 2θ = 11.3°, 23.5°, 34°, and 60.3°.
[0033] The fibrous rod-shaped manganese-rich precursor comprises the following raw materials: a manganese-containing mixed salt solution, a phosphate solution, a precipitant, an oxidant, and an A metal salt solution. The manganese-containing mixed salt solution is either a nickel-manganese mixed metal salt solution or a nickel-cobalt-manganese mixed metal salt solution.
[0034] Manganese-containing mixed salt solutions include one or more of sulfates, chlorides, nitrates, and acetates.
[0035] The concentration of the manganese-containing mixed salt solution is 1.0~3.0 mol / L.
[0036] In a manganese-containing mixed salt solution, the proportion of each element can be determined by the range defined by the general formula x, y, and z: Example as follows: In nickel-manganese mixed salt solutions: the molar ratio of nickel to manganese is 13:87~47:53; When using a mixed nickel-cobalt-manganese salt solution, the molar ratio of nickel, cobalt, and manganese is 12:1:87 to 46:1:53 (based on the maximum cobalt content).
[0037] The phosphate solution concentration is 0.25~1.0 mol / L. Phosphates include one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, sodium monofluorophosphate, and ammonium monofluorophosphate.
[0038] The precipitant includes one or both of NaOH solution and KOH solution; the concentration of the precipitant is 2.7~10.8 mol / L.
[0039] Oxidizing agents include one or more of the following: nitrogen-oxygen mixture, hydrogen peroxide solution, ammonium thiosulfate solution, and sodium thiosulfate solution.
[0040] The oxygen content of the nitrogen-oxygen mixture is preferably 5-10%; the concentrations of the hydrogen peroxide solution, ammonium thiosulfate solution, and sodium thiosulfate solution are preferably 0.05-0.5 mol / L.
[0041] The oxidant is further preferably a nitrogen-oxygen mixture with an oxygen content of 5% or a 0.1 mol / L hydrogen peroxide solution.
[0042] Preferably, the oxidant enters the reactor via a liquid-phase pipeline, with the outlet located in the middle layer of the double-layer stirring tank.
[0043] The concentration of metal salt A is 0.1~0.5 mol / L. The raw material for metal salt A is selected from one or more soluble metal salts selected from Mn, Al, Fe, Ti, Zr, Nb, Mo, and W. For example, it can be sodium aluminate, ferric sulfate, titanium oxysulfate, zirconium sulfate, niobium oxalate, sodium molybdate, sodium valerate, etc.
[0044] In the A metal salt solution, metal A can be one or more; If A is a single salt, it can be prepared simultaneously with other salts such as sulfate or nitrate, but in practice, a single salt is more commonly used. If A consists of two elements, solutions need to be prepared for both. Whether to mix them depends on whether the salt solutions can coexist. If they cannot coexist, they need to be added separately.
[0045] The molar ratio of manganese in a manganese-containing mixed metal salt to metal A in a metal A salt is 75:1 to 25:6.
[0046] The molar ratio of the oxidant to metal A in metal salt A is 1:5 to 5:1.
[0047] The molar ratio of phosphate ions in phosphate to metal A in metal A salt is 1:1 to 12:1. The amount of phosphate used is related to x, and the range of x values has been given. x includes x1 + x2, and the relationship between x1 and the amount of phosphate used will not be elaborated here.
[0048] This application also provides a method for preparing a fibrous rod-shaped manganese-rich precursor, comprising the following steps: Step 1: In the reactor, the precipitant is mixed with water to obtain the bottom liquid; the temperature in the reactor is controlled at 30~60℃ and the stirring speed is 550~700rpm, and an inert atmosphere is introduced to make the reaction system a slightly positive pressure state.
[0049] The preferred range for micro-positive pressure is 0.01-0.1 MPa.
[0050] The pH value of the base solution is 10.0~11.0.
[0051] Step 2: Maintaining the rotation speed of Step 1, add manganese mixed salt solution, phosphate solution and metal A salt solution to the reactor in a uniform and co-current manner, and add oxidant. Adjust the amount of precipitant added to keep the pH of the reaction system at 10.0~11.0 and react for 60~90 minutes.
[0052] The precipitant was added at a constant rate and in parallel with the manganese-containing mixed salt solution, phosphate solution, and metal A salt solution.
[0053] Step 3: Adjust the pH of the reaction system by adjusting the amount of precipitant added to make the pH 9.0~10.0, and continue to add oxidant. Adjust the stirring speed to 450~600 rpm, and react at 30~60℃ for 50~60 hours. Then turn off the oxidant to obtain the slurry.
[0054] The slurry was washed with water, centrifuged, dehydrated and dried under nitrogen protection to obtain a fibrous rod-shaped manganese-rich precursor.
[0055] The pH reduction rate in steps 2 to 3 is 0.05~0.2 / h, and the rotation speed is reduced at a uniform rate.
[0056] A precipitant needs to be added in all steps 1-3. Step 1 is for adjusting pH to create nuclei, and steps 2-3 are for adjusting pH to grow (the precipitant is continuously introduced during the synthesis stage, and the pH is adjusted by controlling the amount).
[0057] Preferably, the fibrous rod-shaped manganese-rich precursor has an average D50 particle size of 2~4μm.
[0058] Preferably, the solid content of the slurry is 550~750g / L.
[0059] Preferably, at the end of the reaction in step 3, the color of the slurry is quantitatively determined using a Lab colorimeter, with an L value of 55-65, an a value of 3-10, and a b value of 15-30.
[0060] The present application will be further described below through specific embodiments.
[0061] Example 1 This embodiment provides a fibrous rod-shaped manganese-rich precursor, and the specific steps are as follows: Step 1: Preparation of the solution to be used: Nickel sulfate and manganese sulfate were weighed according to a nickel-manganese molar ratio of 0.344:0.656, dissolved in deionized water, and a 2 mol / L nickel-manganese mixed salt solution was prepared.
[0062] Prepare a 0.25 mol / L sodium dihydrogen phosphate solution using deionized water as the solvent.
[0063] A 5 mol / L sodium hydroxide solution was prepared using deionized water as a solvent to obtain a precipitant.
[0064] A 0.1 mol / L hydrogen peroxide solution was prepared using deionized water as a solvent to obtain the oxidant.
[0065] A 0.1 mol / L sodium aluminate solution was prepared using deionized water as the solvent to obtain a solution of metal salt A.
[0066] Step 2: Add pure water and precipitant to the reactor to prepare a bottom solution with a pH of approximately 10.8. Heat the solution to 40°C, maintain a stirring speed of 650 rpm, and introduce nitrogen at a rate of 30 L / min, keeping the reactor under positive pressure. (Regarding the "~", "~" means approximately equal to; in actual engineering control, there may be a deviation of 0.05 fluctuations; the same applies below, and will not be elaborated further.) Step 3: Keep the stirring speed at 650 rpm, add nickel-manganese mixed salt solution, sodium dihydrogen phosphate solution and sodium aluminate solution to the reactor with the prepared bottom liquid in a uniform and co-current manner, and add hydrogen peroxide solution. Adjust the amount of precipitant to make the pH of the reaction system ~10.5 and react for 90 min.
[0067] The precipitant was added together with the nickel-manganese mixed salt solution, sodium dihydrogen phosphate solution, and sodium aluminate solution in a uniform, parallel flow.
[0068] The molar ratio of sodium dihydrogen phosphate to sodium aluminate is 9:2; The molar ratio of manganese in the sodium dihydrogen phosphate and nickel-manganese mixed salt is 9:67; The molar ratio of the oxidant hydrogen peroxide solution to the sodium aluminate solution is 7:2.
[0069] Step 4: Adjust the flow rate of the precipitant to lower the pH at a frequency of 0.1 / h, so that the final growth pH is ~9.0. Continue to introduce the oxidant and continuously and uniformly reduce the stirring speed. When the reaction reaches 15h, the stirring speed is 550rpm. The material in the reactor is discharged into the thickener for cleaning and solidification. The reaction is continued at 40℃ for 50h. When the Malvern particle size test shows Dv50~3.0μm, stop the liquid feeding and turn off the oxidant. The resulting slurry has qualified particle size.
[0070] The color of the slurry was quantitatively determined using a Lab colorimeter, and the measured values were L = 55.65, a = 7.42, and b = 21.37.
[0071] Under nitrogen protection, a fibrous rod-shaped manganese-rich precursor was obtained by washing with water, centrifugation, dehydration, and drying, with the molecular formula [Ni]. 0.31 Mn 0.6 (Al) 0.02 Mn 0.07 )(OH) 1.82 (PO4) 0.09 The phosphorus doping content is approximately 10,000 ppm.
[0072] Surface and cross-sectional SEM and XRD images of the manganese-rich fibrous rod-shaped precursor in Example 1 are shown below. Figure 1 .
[0073] Example 2 This embodiment provides a fibrous rod-shaped manganese-rich precursor, and the specific steps are as follows: Step 1: Weigh out nickel sulfate and manganese sulfate according to a nickel-manganese molar ratio of 0.335:0.665 and dissolve them in deionized water to prepare a 2 mol / L nickel-manganese mixed salt solution. Prepare a 0.25 mol / L sodium dihydrogen phosphate solution. Use a 5 mol / L sodium hydroxide solution as a precipitant. Mix compressed air and nitrogen in a 1:3 volume ratio and introduce the oxidant into a gas transfer tank (oxygen content ~5%) for later use. Prepare a 0.1 mol / L ferrous sulfate solution. (Regarding ferrous sulfate, ferrous ions are easily oxidized; after introducing the oxidant during the synthesis process, they are converted to ferric iron.) Step 2: Add pure water and precipitant to the reactor to prepare a bottom solution with pH ~10.5, and heat it to 40℃. Stir at 650 rpm and introduce nitrogen at a rate of 30 L / min to maintain positive pressure in the reactor.
[0074] Step 3: Add nickel-manganese mixed metal salt solution, precipitant (continuously introduced to adjust pH), sodium dihydrogen phosphate solution and ferrous sulfate solution to the reactor with the prepared base solution in a uniform and co-current manner, and introduce oxidant to make the reaction system pH ~10.5 and react for 90 min.
[0075] The molar ratio of sodium dihydrogen phosphate to ferrous sulfate solution is 6:2; The molar ratio of manganese in the sodium dihydrogen phosphate and nickel-manganese mixed salt is 6:65; The molar ratio of oxygen to ferrous sulfate solution in the oxidant is 4:2.
[0076] Step 4: Adjust the flow rate of the precipitant to lower the pH at a frequency of 0.1 / h until the final growth pH reaches 9.5. Continue to introduce the oxidant and continuously and uniformly decrease the stirring speed. After 15 hours of reaction, the stirring speed is set to 550 rpm. The reactor material is then discharged into a thickener for cleaning and solidification. The reaction is continued at 40℃ for 55 hours. When the Malvern particle size test shows Dv50~3.0μm, the liquid feeding is stopped, the oxidant is turned off, and the resulting slurry has a qualified particle size.
[0077] The color of the slurry was quantitatively determined using a Lab colorimeter, with an L value of 58.16, an a value of 6.87, and a b value of 27.56.
[0078] Under nitrogen protection, a fibrous rod-shaped manganese-rich precursor was obtained by washing with water, centrifugation, dehydration, and drying, with the molecular formula [Ni]. 0.33 Mn 0.61 (Fe) 0.02 Mn 0.04 )(OH) 1.88 (PO4) 0.06 The phosphorus doping content is approximately 6500 ppm.
[0079] Example 2: Surface and cross-sectional SEM and XRD images of the fibrous rod-shaped manganese-rich precursor (refer to...) Figure 2 .
[0080] Comparative Example 1 This comparative example provides a manganese-rich precursor, and the specific steps are as follows: Step 1: Weigh out nickel sulfate and manganese sulfate according to a nickel-manganese molar ratio of 0.35:0.65, dissolve them in deionized water to prepare a 2 mol / L nickel-manganese mixed salt solution, prepare a 0.25 mol / L sodium monofluorophosphate solution, use a 5 mol / L sodium hydroxide solution as a precipitant, and mix compressed air and nitrogen in a 1:3 volume ratio and introduce the mixture into a gas transfer tank with an oxygen content of ~5% for later use.
[0081] Step 2: Add pure water and precipitant to the reactor to prepare a bottom solution with pH ~10.5, and heat it to 40℃. Stir at 650 rpm and introduce nitrogen at a rate of 30 L / min to maintain positive pressure in the reactor.
[0082] Step 3: Add nickel-manganese mixed salt solution, precipitant (continuously introduced to maintain and adjust pH), and phosphate solution to the reactor with the prepared base solution in a uniform and co-current manner, and introduce oxidant to make the reaction system pH ~10.5 and react for 90 min.
[0083] The molar ratio of manganese in the sodium monofluorophosphate and nickel-manganese mixed salt is 1:65; The molar ratio of oxygen to sodium monofluorophosphate in the oxidant is 1:1.
[0084] Step 4: Adjust the pH at a frequency of 0.1 / h until the final growth pH reaches ~10, and continuously introduce oxidant. Continuously and uniformly reduce the stirring speed until 15h, at which point the stirring speed is 550rpm. The reactor material is then sent to a thickener for rinsing and solidification. The reaction is continued at 40℃ for 60h. When the Malvern particle size test shows Dv50~3.0μm, stop the liquid feeding and turn off the oxidant. The resulting slurry has qualified particle size.
[0085] The color of the slurry was quantitatively determined using a Lab colorimeter, with an L value of 61.03, an a value of 5.24, and a b value of 23.47.
[0086] Under nitrogen protection, after washing with water, centrifugation, dehydration, and drying, a spherical manganese-rich precursor with the molecular formula [Ni] was obtained. 0.35 Mn 0.64 (Mn) 0.01 )(OH) 1.98 (PO4) 0.01 The phosphorus doping is approximately 3300 ppm.
[0087] Surface and cross-sectional SEM and XRD images of the manganese-rich precursor in Comparative Example 1 are shown below. Figure 3 .
[0088] Comparative Example 2 This comparative example provides a method for preparing a manganese-rich cathode precursor. The steps are basically the same as those in Example 1, except that: in step 1, no phosphate solution is prepared; in steps 3 and 4, nitrogen protection is maintained throughout the reaction process, and a nickel-manganese mixed salt solution, precipitant, and oxidant are introduced, but no phosphate solution is introduced.
[0089] Surface and cross-sectional SEM and XRD images of the manganese-rich precursor in Comparative Example 2 are shown below. Figure 4 .
[0090] Comparative Example 3 This comparative example provides a method for preparing a manganese-rich cathode precursor. The steps are basically the same as those in Example 1, except that: in step 1, no phosphate solution and oxidant are prepared; in steps 3 and 4, nitrogen protection is maintained throughout the reaction process, and no phosphate solution and oxidant are introduced.
[0091] Surface and cross-sectional SEM and XRD images of the manganese-rich precursor in Comparative Example 3 are shown below. Figure 5 .
[0092] To verify the advancement of the preparation method of the fibrous rod-shaped manganese-rich precursor provided in the embodiments of this application, the fibrous rod-shaped manganese-rich precursors of Examples 1-2 and the manganese-rich cathode precursors of Comparative Examples 1-3 were tested and calculated for Dv50, diameter, specific surface area, tap density, porosity, average thickness and size of primary particles, average thickness and size of internal laths, and sphericity and aspect ratio of secondary particles. The results are shown in Table 1 below.
[0093] Specifically, Dv50 was tested using a Malvern laser particle size analyzer; tap density was tested using a Dandong Best tap density analyzer; specific surface area was tested using a Best nitrogen adsorption specific surface area analyzer; porosity, secondary particle sphericity and aspect ratio, and the average thickness and size of primary and secondary particles were measured using graphic measurement software and length measurement software on electron micrographs; electron microscopy and cross-sectional electron microscopy were performed using high-resolution field emission scanning electron microscopes from Zeiss or Thermo Fisher Scientific.
[0094] Table 1
[0095] From Table 1 and the attached figures, at least the following conclusions can be drawn: The fibrous rod-shaped manganese-rich precursor prepared by the method provided in this application, through an oxidation process to control the hydroxide and expand the interlayer spacing, synergistically introduces exogenous high-valence metal cations A (n≥3) and in-situ oxidized Mn into the interlayer. This balances the net positive charge generated on the interlayer, driving negatively charged phosphate anions into the interlayer region and embedding them into the lattice, replacing some of the hydroxide ions (OH). - Due to its large size, the phosphate group, after oxidation, leads to a significant increase in interlayer spacing through intercalation, thus achieving high-concentration doping of phosphorus in the precursor. Ni-Mn phosphate has a three-dimensional network structure, and the prepared precursor exhibits a fibrous rod morphology with a large specific surface area, providing abundant channels for the rapid transport of lithium ions within the cathode material, thereby significantly improving the material's rate performance. Furthermore, the high concentration of phosphate and cation doped layered structures exacerbates the intercalation phenomenon, leading to lattice distortion and reducing the overall orderliness of the layered structure. Morphologically, this results in a secondary spherical to rod-shaped LDH structural transformation. The disordered configuration has a higher energy barrier for oxygen rearrangement, kinetically suppressing irreversible oxygen evolution, reducing lattice oxygen loss, and maintaining structural integrity.
[0096] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.
Claims
1. A fibrous rod-shaped manganese-rich precursor, characterized in that, The molecular formula is [Ni 1-x-y-z Co y Mn z R x (OH) 2-2x (PO4) nx / 3 ;0.03≤x≤0.12, 0≤y≤0.1, 0.5≤z≤0.75; R x For A x1 Mn x2 x1 + x2 = x, A is an n-valent metal ion, R x In this case, Mn and A are both n-valent, n≥3, 0.01≤x1<0.12, 0<x2≤0.
11.
2. The fibrous rod-shaped manganese-rich precursor according to claim 1, characterized in that, The primary particles of the fibrous rod-shaped manganese-rich precursor have a slender, elongated shape and are stacked in layers along the 001 crystal plane.
3. The fibrous rod-shaped manganese-rich precursor according to claim 1, characterized in that, The average D50 of the fibrous rod-shaped manganese-rich precursor is 2~4 μm; The average pore volume of the fibrous rod-shaped manganese-rich precursor is 0.2~0.6 cm³. 3 / g; The specific surface area of the fibrous rod-shaped manganese-rich precursor is 50~100m². 2 / g; The tap density of the fibrous rod-shaped manganese-rich precursor is 0.8~1.3 g / cm³. 3 .
4. The fibrous rod-shaped manganese-rich precursor according to claim 1, characterized in that, The fibrous rod-shaped manganese-rich precursor comprises the following raw materials: a manganese-containing mixed salt solution, a phosphate solution, a precipitant, an oxidant, and an A metal salt solution; The molar ratio of manganese to metal A in manganese-containing mixed salts is 75:1 to 25:
6. The molar ratio of the oxidant to metal A in metal salt A is 1:5 to 5:1; The molar ratio of phosphate ions in phosphate to metal A in metal A salt is 1:1 to 12:
1.
5. The fibrous rod-shaped manganese-rich precursor according to claim 4, characterized in that, The manganese-containing mixed salt solution is a nickel-manganese mixed salt solution or a nickel-cobalt-manganese mixed salt solution.
6. The fibrous rod-shaped manganese-rich precursor according to claim 5, characterized in that, Manganese-containing mixed salt solutions include one or more of sulfates, chlorides, nitrates, and acetates.
7. The fibrous rod-shaped manganese-rich precursor according to claim 4, characterized in that, The phosphate in the phosphate solution includes one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, sodium monofluorophosphate, and ammonium monofluorophosphate. The precipitant includes one or both of NaOH solution and KOH solution; The oxidant includes one or more of the following: a nitrogen-oxygen mixture, hydrogen peroxide solution, ammonium thiosulfate solution, and sodium thiosulfate solution; The metal salt solution A includes solutions containing one or more soluble metal salts selected from Mn, Al, Fe, Ti, Zr, Nb, Mo, and W.
8. The fibrous rod-shaped manganese-rich precursor according to claim 4, characterized in that, The concentration of the manganese-containing mixed salt solution is 1.0~3.0 mol / L; The concentration of the phosphate solution is 0.25~1.0 mol / L; The concentration of the precipitant is 2.7~10.8 mol / L; The concentration of the metal salt A solution is 0.1~0.5 mol / L.
9. A method for preparing a fibrous rod-shaped manganese-rich precursor according to any one of claims 1-8, characterized in that, Includes the following steps: The precipitant is mixed with water to obtain a bottom solution with a pH value of 10.0~11.0; Under conditions of 30~60℃, stirring speed of 550~700rpm, and inert atmosphere, the base liquid, manganese mixed salt solution, phosphate solution, metal A salt solution, and oxidant are mixed and reacted at pH 10.0~11.0 for 60~90min. After the above reaction is completed, the mixture is reacted for 50-60 hours under the conditions of pH 9.0-10.0, temperature 30-60℃, and continuous oxidant flow to obtain the slurry. The precipitant is continuously introduced during the above preparation process, and the pH is adjusted by controlling the amount of precipitant introduced. The slurry was washed, centrifuged, dehydrated, and dried to obtain a fibrous rod-shaped manganese-rich precursor.
10. The method for preparing the fibrous rod-shaped manganese-rich precursor according to claim 9, characterized in that, The color of the slurry was quantitatively determined using a Lab colorimeter; the L value of the slurry was 55~65, the a value was 3~10, and the b value was 15~30.